SOCIAL FOUNDATIONS OF DOMESTIC VIOLENCE: A CASE STUDY OF DOMESTIC VIOLENCE IN THE CONTEXT OF CHINA - Liu, Zhitong (PEOPLE: International Journal of Social Sciences, 2017)
Previous and current sociology scholars have come up with several theories to answer the question "why do men use violence?". Up to this day, it is believed that current sociological literatures are divided into three perspectives: family violence perspective, feminist perspective and integrative perspective. This paper upholds an integrated theory of resource theory, feminist perspective and socio-demographic perspective. In this paper, we situated the theory in Chinese society and selected five cases based on Oral Accounts of Battered Women in China to test the validity of the theory. The findings confirm the theory and further suggest that the domestic violence should be regarded as a problem from a societal level. In other words, tackling the problem individually would not be adequate and efficient.